PENDAMPINGAN KELOMPOK TERNAK DALAM PEMBUATAN MINERAL BLOK HERBAL DI DESA MARENU KECAMATAN AEK NABARA BARUMUN KABUPATEN PADANG LAWAS - Fajrin, Muharram; Nurmi, Aisyah; Harahap, Nurainun (Universitas Muhammadiyah Tapanuli Selatan, 2018)
This activity has been conducted in February to March 2017 in the village of Marenu sub-district of Aek Nabara Padanglawas District with partnersAdvanced Livestock Group Jaya with the aim to increase knowledge of the breeder about the processing of feed sheep and lamb weight disorders as well as mineral technology blocks transfer herbs.A special target in this program is producing herbal mineral products to accelerate weight gain local sheep. The product is potentially for patents, publications, appropriate technology, and textbook enrichment and increases the income of local sheep rancher above the UMR. The approach method does include phases: (a) Dissemination of herbal mineral technology program in an effort to overcome the local sheep weight disorders; (b) the preparation of the social preconditions, namely the strengthening of local sheep farmer groups, either group or forum as a media meet and problem solving-problems encountered breeder; (c) mineral technology program execution herbs both technical and nontechnicalfor the breeder community, supported by related agencies (local government and higher education (Faculty of animal husbandry, Muhammadiyah University of South Tapanuli); (d) Monitoring, evaluation and reporting. The results obtained are very satisfactory known breeders, among others, as follows: 1.) all cattle like the mineral blocks, 2) livestock appetite grew, 3)herding cattle so much faster, 4) livestock quieter moments infree-range, 5). cattle drinking increased and 6)the addition of the weight of the body of livestock.Â Keywords:Local Lamb, Mineral Blocks, Appetite, Body Weight.